Neonatal Bartter syndrome and unilateral ectopic renal cyst as new renal causes of hydrops fetalis: two case reports and review of the literature. (July 2013) - Çetinkaya, Merih; Durmaz, Oguzhan; Büyükkale, Gökhan; Ozbek, Sibel; Acar, Deniz; Kılıcaslan, Isın; Kavuncuoglu, Sultan
Abstract Non-immune hydrops fetalis (NIHF) is a challenging entity as it represents the end stage of several different disorders. Renal and genitourinary causes of NIHF are rare and include congenital renal malformations, tumors and ureter-urethra disorders. Herein, two NIHF cases with different renal causes were presented. The first case that had antenatal NIHF was diagnosed neonatal Bartter syndrome. The second case of NIHF with antenatal large cyst in the surrenal gland area required surgery and ectopic renal cyst was diagnosed. To our best of knowledge, these are the first reports of NIHF associated with neonatal Bartter syndrome and ectopic renal cyst in neonates. Although it may be coincidental, these cases suggest that both neonatal Bartter syndrome and unilateral ectopic renal cyst may cause NIHF development in neonates by several different mechanisms. Therefore, these two rare entities should be suspected in cases of NIHF with similar findings.